2022
DOI: 10.1002/jcla.24303
|View full text |Cite
|
Sign up to set email alerts
|

Role of m5C RNA methylation regulators in colorectal cancer prognosis and immune microenvironment

Abstract: Background RNA modification has become one of the hot topics of research as it can be used for tumor prognosis. However, its role in various biological processes is still poorly understood. The aim of this study was to investigate the role of m5C and m1A regulators on colorectal cancer prognosis using bioinformatics tools. The association between these regulators and differences in patient survival as well as the clinicopathological characteristics and tumor immune microenvironment in colorectal cancer tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…NSUN6 expression could predict prognosis in both breast and colorectal cancer. However, NSUN6 expression was associated with a poor prognosis in breast cancer, and with a more favorable prognosis in colorectal cancer (Huang et al, 2021b;Fang et al, 2022). In the present study, NSUN6 expression was associated with a longer survival.…”
Section: Discussioncontrasting
confidence: 40%
“…NSUN6 expression could predict prognosis in both breast and colorectal cancer. However, NSUN6 expression was associated with a poor prognosis in breast cancer, and with a more favorable prognosis in colorectal cancer (Huang et al, 2021b;Fang et al, 2022). In the present study, NSUN6 expression was associated with a longer survival.…”
Section: Discussioncontrasting
confidence: 40%
“…This suggests a link between methylation levels and immune cell in ltration. In colorectal cancer, DNA methyltransferase DNMT3A was found to be associated with in ltration of six major immune cells [41]. One study revealed that NEFM DNA methylation was moderately to strongly negatively associated with in ltration levels of B cells, CD8 + T cells, CD4 + T cells, macrophages, neutrophils, and dendritic cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cluster C was characterized by a higher number of immunocytes and immune response reactions, which included a greater abundance of plasmacytoid dendritic cells (pDCs) and interferon receptors, the former of which are increased in MM patients’ bone marrow and play a key role in the progression of MM ( Ray et al, 2015 ). Moreover, pDCs are observed in m 5 C regulators, including the DNMT3A and NSUN family, and are regulated by interferon receptors ( Bi et al, 2018 ; Fang et al, 2022 ). All three m 5 C clusters may have abundant metabolism-related pathways, which can help guide the identification of key m 5 C regulators and immune characteristics of MM.…”
Section: Discussionmentioning
confidence: 99%